Possible roles of the hereditary hemochromatosis protein, HFE, in regulating cellular iron homeostasis - CAROLINE A ENNS (Biological Research, 2006)
Hereditary hemochromatosis (HH) is the most common inherited disorder in people of Northern European descent. Over 83% of the cases of HH result from a single mutation of a Cys to Tyr in the HH protein, HFE. This mutation causes a recessive disease resulting in an accumulation of iron in selected tissues. Iron overload damages these organs leading to cirrhosis of the liver, diabetes, cardiomyopathy, and arthritis. The mechanism by which HFE influences iron homeostasis in cells and in the body remains elusive. Lack of functional HFE in humans produces the opposite effects in different cell types in the body. In the early stages of the disease, Kupffer cells in the liver and enterocytes in the intestine cells are iron depleted and have low intracellular ferritin levels, whereas hepatocytes in the liver are iron overloaded and have high intracellular iron levels. This review gives the background and a model as to possible mechanisms of how HFE could exert different effects on iron homeostasis in different cell types.